Impact Assessment of dairy based interventions under Farmer FIRST Programme of ICAR-NDRI - Kamble, Parshuram; Sankhala, Gopal (Indian Farming, 2021)
Dairying is a sub-sector in agriculture and a prominent subsidiary enterprise which gives income, gainful employment, food, nutritional and livelihood security to the millions of farm families. Dairy farming forms an essential part of Haryana’s rural economy. The present study was conducted in the Farmer FIRST Progromme area in 5 villages of Karnal district namely Kamalpur Roran, Garhi Gujran, Nagala Roran, Churni and Samoura. Under dairy based interventions, 7 interventions were selected and 184 respondents were selected in proportion to the intervention. The economic impact assessment of the interventions was undertaken and the benefit-cost ratio obtained are as follows: Balanced feeding (1.86), Bypass fat supplementation (2.99), Mineral mixture supplementation (5.37), Theileriosis vaccination (74.88), Theileriosis treatment (10.19), Mastitis diagnosis (41.20) and treatment of mastitis (85.75).